Epidemiology of Sports-Related Eye Injuries Among Athletes in Tianjin, China - Zhang, Jingkai; Zhu, Xinlei; Sun, Zhiyong; Wang, Jiaxing; Sun, Zhuoyu; Li, Jianan; Huang, Yunli; Wang, Tian; Xie, Ruotian; Han, Han; Zhao, Xiao; Song, Yinting; et al. (Frontiers in Medicine, 2021)
Purpose: To investigate the incidence, characteristics, and risk factors of sports-related eye injuries among athletes in Tianjin, China. Methods: A cross-sectional study was carried out from March 2018 to October 2018. In this study, the athletes from Tianjin University of Sports, Tianjin Vocational College of Sports, and Tianjin provincial sports teams were selected for general investigation. In total, 1,673 athletes were invited and 1,413 participated in the study (response rate of 84.5%). Results: In total, 1,413 athletes were enrolled; 151 had suffered from sports-related eye injuries, with an incidence of 10.7% (95% CI: 9.1–12.0%). Handball (38.5%) was the sport with the highest incidence of eye injuries, followed by water polo (36.4%) and diving (26.7%). Overall, 42.4% of the athletes were injured by ball and 22.5% of injuries came from teammates. The eye injuries usually occurred during training (64.2%) and competitions (14.6%). Adnexa wound (51.7%) was the most common type of injury. About 11.9% of the athletes with eye injuries had the impaired vision; 66.7% failed to see doctors on time. The athletes <18 years of age had a higher risk of eye injuries (odds ratio [OR] =1.60, 95% CI: 1.06–2.40). The athletes with lower family income (<1,000 RMB) were at risk population for sports-related eye injuries (OR = 3.91, 95% CI: 2.24–6.82). Training >4 h a day increased the risk of eye injuries (OR = 2.21, 95% CI: 1.42–3.43). Conclusion: The incidence of sports-related eye injuries among athletes was 10.7% in Tianjin, China. Handball, water polo, and diving were the most common activities of injury. Age, family income, and training time were the risk factors for sports-related eye injuries.